Karma-Dharma Dynamics: Rethinking Religion in “Yatri,” “The Brave Little Parrot,” and “If Not Higher” - Dhungel, Nabaraj (Journal of Productive Discourse, 2025)
This article presents a humanistic analysis of Laxmi Prasad Devkota’s poem “Yatri,” Rafe Martin’s retelling of the Buddhist legend “The Brave Little Parrot,” and Isaac Leib Peretz’s story “If Not Higher.” It argues that these works champion the idea that true dharma—or religion—is grounded in karma, the practice of humanity. The texts suggest that the essence of being human lies in treating others with compassion, dignity, and respect, without discrimination or dehumanization. When religion is reduced to rituals and temple visits, while ignoring human suffering, it loses its spiritual core. The article contends that failing to act humanely, even under the guise of religious duty, betrays the very foundation of dharma. Drawing on the philosophies of humanist thinkers such as Auguste Comte, Jeaneane D. Fowler, and Jim Herrick, the research emphasizes that selfless service to the helpless and marginalized transcends religious boundaries and embodies the highest moral calling. Devkota, Martin, and Peretz all highlight that genuine spirituality lies in aiding others without bias or expectation. Their stories urge a shift from orthodox practices to acts that preserve and uplift humanity. The article reveals that in a world rife with division and dogma, recognizing humanity as the truest form of religion is both a moral necessity and a universal truth. This perspective calls for a transformative understanding of religion—one rooted not in doctrine but in action, empathy, and the shared responsibility of sustaining human dignity.